Motion sickness susceptibility among Malaysians when travelling in a moving vehicle - Md. Yusof, Nidzamuddin; Mohamad Ruse, Dzulfadhli; Sanusi, Nortazi; Karjanto, Juffrizal; Hassan, Muhammad Zahir; Sulaiman, Syabillah; Mohd Jawi, Zulhaidi; Abu Kassim, Khairil Anwar (Universiti Malaysia Pahang, 2023)
Motion sickness is a common problem when travelling in a moving vehicle, especially on land transportation. This occurrence would signify when users are exposed to unexpected movement in an obstructed view. Each user can experience a different level of motion sickness, depending on their susceptibility. This paper aims to study the motion sickness susceptibility among Malaysians using Motion Sickness Susceptibility Questionnaires (MSSQ-Short). A total of 252 Malaysians (146 males and 106 females) completed a set of questionnaires. The questionnaire was distributed through electronic means such as Facebook, WhatsApp, Twitter, and email and consisted of demographic, MSSQ-Short, travel experience as a driver and passenger, and seating position. This study provides a correlation between experiencing motion sickness between childhood and adulthood (r = 0.124, p < 0.05) for the Malaysian sample. This study concludes that Malaysian susceptibility is higher compared to other countries.